MANAJEMEN KOMUNIKASI DINAS PARIWISATA KEPEMUDAAN OLAHRAGA DAN KEBUDAYAAN DALAM MENGEMBANGKAN DESTINASI WISATA PANTAI SOLOP DI KABUPATEN INDRAGIRI HILIR - Refza Munami; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Solop beach tourism was a tourist destination in Mandah at Indragiri Hilir district. Solop beach was one of the attractions in the downstream Indragiri district. The government made various efforts to improve tourism facilities and promotions in order to attract tourists who come to Solop Beach. This showed the government's seriousness to develop solop beach tourism.This study aimed to analyze the communication management carried out by the Youth and Sports Tourism and Culture Office of Indragiri Hilir Regency. In the form of planning, organizing, mobilizing, monitoring and evaluating communication in the development of the Solop beach in Indragiri Hilir Regency. This study used a qualitative research method with a descriptive approach. Qualitative research method was a research method based on post-positivism philosophy, it used to examine the condition of natural objects (as opposed to experiments). Data analysis were inductive/qualitative and quality research results emphasize meaning rather than generalizationSolop Beach Tourism used several promotional media that are sufficient to support the marketing of Solop Beach tourism, including posters, banners, billboards and guidebooks for the location of Solop Beach. Evaluation of activities made progress on communication management using social media in promoting Solop Beach Tourism that people can see that social media was very fast in its delivery to the community and evaluates a joint activity that had been carried out by the Department of Tourism, Youth and Sports, and Culture of Indragiri Hilir Regency, village government and Public.in the medium category Keywords: Tourism, Media Promotions, Solop Beach